Comparison of Absolute Neutrophil Count between Hospital and Community Acquired Methicillin-Resistant Staphylococcus aureus Infection - Kurniyanto, Kurniyanto; Santoso, Widayat Djoko; Nainggolan, Leonard; Kurniawan, Juferdy (UI Scholars Hub, 2018)
Introduction. The virulence factors from community acquired-methicillin resistant Staphylococcus aureus (CA-MRSA) mainly due to toxins like Panton Valentin Leukocidin (PVL) and Phenol Soluble Modulin (PSM). Both of toxins cause decrease of value through neutrophil lysis. This study aimed to identify different value of absolute neutrophil count between hospital and community acquired MRSA. Methods. A cross sectional was conducted which included subjects who were infected by MRSA and hospitalized during 2012-2017. Classification of MRSA were divided due to its sensitivity and resistance to non-beta lactam antibiotics. Isolate that resistance to ≤ 2 antibiotics were classified as CA-MRSA. The others with resistance to ≥ 3 antibiotics were classified as hospital acquired MRSA. Absolute neutrophils count (ANC) were collected 24 hours from the positive MRSA culture. Data were analyzed by using independent T test and Mann-Whitney test. Results. We collected 62 subjects infected by MRSA which 35 subjects were HA-MRSA and 27 subjects were CA-MRSA. The median of ANC from CA-MRSA was 7,410.7 (1,147.3-26,560.2) and HA-MRSA was 16,198.0 (3,921.6-28,794.1) with p value < 0.001. Conclusion. There was a different value of absolute neutrophil count in infections due to community and hospital acquired MRSA.